2011
DOI: 10.3201/eid/1706.101067
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Seroprevalence and Chronic Infections in Patients with HIV, Switzerland

Abstract: We screened 735 HIV-infected patients in Switzerland with unexplained alanine aminotransferase elevation for hepatitis E virus (HEV) immunoglobulin G. Although HEV seroprevalence in this population is low (2.6%), HEV RNA can persist in patients with low CD4 cell counts. Findings suggest chronic HEV infection should be considered as a cause of persistent alanine aminotransferase elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
105
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 14 publications
9
105
3
Order By: Relevance
“…However, HEV co-infection in patients with HIV is not common and, to date, less than 20 cases have been documented in the literature, and only a handful have had chronic infection, the majority of these cases become cleared of HEV spontaneously. 4,[62][63][64][65][66][67][68][69][70][71][72] In contrast to recipients of a SOT, the key risk factor that determines the development of chronic infection in HIV patients is a low CD4 count. In the five chronic cases described so far, all had CD4 counts <250 mm 3 .…”
Section: Hev Infection In Hiv Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HEV co-infection in patients with HIV is not common and, to date, less than 20 cases have been documented in the literature, and only a handful have had chronic infection, the majority of these cases become cleared of HEV spontaneously. 4,[62][63][64][65][66][67][68][69][70][71][72] In contrast to recipients of a SOT, the key risk factor that determines the development of chronic infection in HIV patients is a low CD4 count. In the five chronic cases described so far, all had CD4 counts <250 mm 3 .…”
Section: Hev Infection In Hiv Patientsmentioning
confidence: 99%
“…[62][63][64][65][66][73][74][75][76][77] One study retrospectively tested for HEV in 194 HIV-positive US military beneficiaries and showed that HEV was the cause of abnormal liver function tests in only 4% of HIV-infected individuals. 65 Serum transaminitis caused by HEV was no more common in this population than in the general population.…”
Section: Hev Infection In Hiv Patientsmentioning
confidence: 99%
“…They described a 48 years old male with abnormal transaminases with a chronically low CD4 count (< 200) despite anti-retroviral treatment, who had persistent HEV RNA in serum for 18 mo and evidence of inflammation and cirrhosis on liver biopsy. Several cases have been reported since then [47][48][49] . All cases of chronic hepatitis E in patients with HIV had CD4 count less than 200.…”
Section: Extra Hepatic Manifestations Of Chronic Hepatitis Ementioning
confidence: 99%
“…All cases of chronic hepatitis E in patients with HIV had CD4 count less than 200. Prevalence of chronic HEV in HIV patients is low and has been reported from 0% to 0.5% in different studies [49][50][51][52] . Recently, few cases of chronic hepatitis E have also been reported in immunocompetent patients [53][54][55] .…”
Section: Extra Hepatic Manifestations Of Chronic Hepatitis Ementioning
confidence: 99%
“…This disease infects about 20 million people and causes 70,000 deaths every year (Rein et al, 2012). The infection is generally acute and largely self-limited, but HEV-infected immunocompromised individuals have a high risk of developing chronic hepatitis (Kenfak-Foguena et al, 2011). …”
Section: Introductionmentioning
confidence: 99%